Morphologic Spectrum of Breast Carcinoma and Correlation of Hormone Receptors and Her2/Neu Status with Clinic-Pathologic Parameters at a Tertiary Care Hospital - Maria Tasneem Khattak, Masroor Hassan, Sarah Javed, Shahid Hasnain, Raazia Mahmood, Ambreen Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: After cardiovascular problems, cancer is the 2nd biggest cause of mortality globally. Globally, breast cancer is recognized as the second most prevalent cancer in general, the most prevalent cancer in women, and the 5th major cause of cancer-related death. Objectives: To study the Morphologic Spectrum of Breast Carcinoma and correlation of hormone receptors and HER2/neu status with clinic-pathologic parameters Methods: A total of 97 consecutive cases of modified radical mastectomy were evaluated in the department of histopathology, Rehman Medical Institute Peshawar from February 2019 to December 2020. Expression of PR, ER and Her2/neu were scored similar to College of American Pathologist’s (CAP) guidelines. The analysis of data was done by using SPSS version. Results: Mean age of presentation was 49.6 years. The most prevalent histological subtype was invasive carcinoma of no particular type (72.2%). Grade II tumors were most frequent (43.3%). Lymphovascular and perineural invasion were present in 53.6% and 40.2% of cases respectively. Pathologic stage pT2 was most frequent (56.7%). Macrometastasis was noted in 61.8% of cases. ER and PR showed positivity in 59.8% and 51.5% of cases and Her2/neu was over expressed in 30.9% of cases. ER positivity inversely correlated with Her2/neu but directly with tumor size. Strong association was found between ER/PR positivity and HER2/neu with histologic grade. Conclusion: Our study showed a diverse spectrum of special type carcinomas, none of which showed HER2/neu over expression. Majority of our patients belong to a younger age group and presented with advanced disease. Triple negative breast cancer (TNBC) was commonest in our population after luminal A. HER2/neu overexpression was limited to grade 2 and 3 of invasive ductal carcinoma